AKTIVITAS PUBLIC RELATIONS PT. P&P BANGKINANG DALAM MENINGKATKAN CITRA MELALUI BANTUAN PERUSAHAAN DIKECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Suriana, Yummi; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
PT Bangkinang Industry and Trade, Pekanbaru City, known as the abbreviation PT P & P Bangkinang. Based on research conducted by the author in the field and also supported by company data that this company has operations that have a negative impact on the environment around the company. The negative impact that occurs is the smell of rubber disrupts the health of residents, especially underage children, which is considered very sensitive and also makes food sellers around the company lose due to the smell of the waste of the company getting stung. The pros and cons of the existence of rubber companies in the midst of residential areas, the occurrence of waste that disrupts the health and comfort of the community. Based on these problems the company overcame it by conducting public relations activities in improving the image through the help of the company.The purpose of this study was to determine the PR activities and obstacles faced in improving the image through company assistance. This study uses a qualitative descriptive research method. Data collection techniques used in this study were interviews, observation and documentation. The subjects involved in this study were determined based on a purposive technique consisting of Deputy Management, Head of Personnel, Assistant Head of Personnel, employees and the community who received CSR program assistance. Data analysis techniques are carried out by using the interactive data analysis model of Miles and Huberman using the technique of checking the validity of the data, namely triagulation of sources and extension of participation.The results of the research in the field, that the activities carried out by PT. Bangkinang P & P Pekanbaru City in enhancing its image through company assistance with internal and external public. Its internal public activities are not yet effective because the company PR does not cooperate with other parties in providing assistance. Whereas the external activities of the PR do not have the media as a tool to improve the image through the assistance of the company. In carrying out public relations activities there are obstacles that the public always complains about is because the company's nominal assistance is fairly minimal.Keyword: Public Relations Activities, Image, Company Assistance.